An overview of satavaptan: a selective V2 receptor antagonist. Issue 4 (July 2010) - Farah, Jareer; Daifallah, Suleiman; Zmily, Hammam; Ghali, Jalal K
Satavaptan is a new selective V2 receptor antagonist that shares the aquaretic effect of the other arginine vasopressin antagonists. Its usefulness has been demonstrated in the correction of hyponatremia as well as in fluid removal in patients with cirrhosis. In addition, animal studies have suggested promising effects in the treatment of several other conditions, such as polycystic kidney disease, renal cell carcinoma, glaucoma, diabetic nephropathy and urinary tract infections. This article reviews the various animal and human studies that have outlined its potential clinical role and provided direction for further research with this drug.